Lack of the Bacterial Phytochrome Protein Decreases Deinococcus radiodurans Resistance to Mitomycin C - Jung, Jong-Hyun; Jeong, Soyoung; Im, Seonghun; Kim, Min-Kyu; Seo, Ho Seong; Lim, Sangyong (Frontiers in Microbiology, 2021)
Deinococcus radiodurans known for its extraordinary resistance to ionizing radiation contains bacterial phytochrome (BphP), a member of the family of red/far-red light-sensing proteins. In this study, we constructed a bphP mutant strain (ΔbphP) to investigate the role of D. radiodurans BphP (DrBphP) in the DNA damage response. When cells were incubated under light and dark conditions following exposure to DNA damaging agents, such as γ- and UV-radiation and mitomycin C (MMC), no significant difference in cell survival was observed between the wild-type D. radiodurans strain (WT) and ΔbphP. However, when continuously exposed to MMC under light conditions, the WT strain notably exhibited increased survival compared to cells grown in the dark. The increased survival was not observed in the ΔbphP strain. These results are indicative of the protective role of light-activated DrBphP in the presence of MMC. Site-directed mutagenesis revealed that the conserved amino acids Cys-24 and His-532 involved in chromophore binding and signal transduction, respectively, were essential for the protective function of DrBphP. Inactivation of the cognate response regulator (DrBphR) of DrBphP increased MMC resistance in the dark, and in trans complementation decreased MMC resistance in the bphP/bphR double mutant strain (ΔbphPR). Considering that DrBphP acts as a light-activated phosphatase that can dephosphorylate DrBphR, phosphorylated DrBphR exerts a negative effect on cell survival in the presence of MMC. DrBphP expression resulted in an increase in MMC resistance of ΔbphPR, implying that other response regulators (RRs) might be involved in the DrBphP-mediated signaling pathway. Of the 12 RR mutant strains, Δdr_0781 demonstrated the same MMC phenotype as ΔbphR, and a further increase in survival was observed in the bphR dr_0781 double mutant strain compared to single mutant, suggesting that DR_0781 may be one of the RRs connected to light and/or DrBphP-dependent MMC sensitivity. This study provided an obvious phenotype for ΔbphP by identifying the conditions under which DrBphP exhibits a fitness advantage.